Participation of Rab5, an Early Endosome Protein, in Hepatitis C Virus RNA Replication Machinery - Stone, Michelle (American Society for Microbiology, 2007)
Like most positive-strand RNA viruses, hepatitis C virus (HCV) is believed to replicate its genome on the surface of rearranged membranes. We have shown previously that HCV NS4AB, but not the product NS4B, inhibits endoplasmic reticulum (ER)-to-Golgi protein traffic (K. V. Konan, T. H. Giddings, Jr., M. Ikeda, K. Li, S. M. Lemon, and K. Kirkegaard, J. Virol. 77:7843-7855). However, both NS4AB and NS4B can induce “membranous web” formation, first reported by Egger et al. (D. B Egger, R. Gosert, L. Bianchi, H. E. Blum, D. Moradpour, and K. Bienz, J. Virol. 76:5974-5984), which is also observed in HCV-infected cells (Y. Rouille, F. Helle, D. Delgrange, P. Roingeard, C. Voisset, E. Blanchard, S. Belouzard, J. McKeating, A. H. Patel, G. Maertens, T. Wakita, C. Wychowski, and J. Dubuisson, J. Virol. 80:2832-2841) and cells that bear a subgenomic NS5A-green fluorescent protein (GFP) replicon (D. Moradpour, M. J. Evans, R. Gosert, Z. Yuan, H. E. Blum, S. P. Goff, B. D. Lindenbach, and C. M. Rice, J. Virol. 78:7400-7409). To determine the intracellular origin of the web, we examined NS4B colocalization with endogenous cellular markers in the context of the full-length or subgenomic replicon. We found that, in addition to ER markers, early endosome (EE) proteins, including Rab5, were associated with web-inducing protein NS4B. Furthermore, an immunoisolated fraction containing NS4B was found to contain both ER and EE proteins. Using fluorescence microscopy, we showed that wild-type and constitutively active Rab5 proteins were associated with NS4B. Interestingly, expression of dominant-negative Rab5 resulted in significant loss of GFP fluorescence in NS5A-GFP replicon cells. We also found that a small reduction in Rab5 protein expression decreased HCV RNA synthesis significantly. Furthermore, transfection of labeled Rab5 small interfering RNAs into NS5A-GFP replicon cells resulted in a significant decrease in GFP fluorescence. Finally, Rab5 protein was found to coimmunoprecipitate with HCV NS4B. These studies suggest that EE proteins, including Rab5, may play a role in HCV genome replication or web formation.